Central nervous system relapse in patients over 80 years with diffuse large B‐cell lymphoma: an analysis of two LYSA studies. (23rd February 2018) - Cabannes‐Hamy, Aurélie; Peyrade, Frederic; Jardin, Fabrice; Emile, Jean‐François; Delwail, Vincent; Mounier, Nicolas; Haioun, Corinne; Perrot, Aurore; Fitoussi, Olivier; Lara, Diane; Delarue, Richard; André, Marc; et al.
Abstract: CNS relapse is reported in 2–5% of diffuse large B‐cell lymphoma (DLBCL) patients, dramatically decreasing overall survival (OS). Very few studies address incidence and risk factors of CNS relapse in very elderly patients, a challenging population to treat given their commonly associated comorbidities. A retrospective analysis was performed of 270 DLBCL patients >80 years treated between 2004 and 2013 in two multicentre phase II LYSA trials (LNH03‐7B, LNH09‐7B) evaluating the addition of rituximab or ofatumumab to mini‐CHOP as front‐line therapy. No patients received CNS prophylaxis. CNS relapse was evaluated according to cumulative incidence, patient characteristics, risk factors, and survival. Median age was 83 years (range: 79–95). After a median follow‐up of 28.7 months, eight patients had CNS relapse (3.0%). Median time between inclusion and CNS relapse was 19.2 months (range: 3.2–32.6). Patients survived a median of 1.5 months after CNS relapse (range: 0.4–4.1). Median OS from relapse was significantly lower in CNS relapse patients (1.5 months, 95% CI: 0.4–3.5) compared to patients with non‐CNS relapse (6.6 months; 95% CI: 4.6–11.9). No baseline characteristics were associated with CNS relapse. The proportion of patients with CNS disease did not differ significantly between patients with low‐intermediate risk according to CNS‐IPI and patients with high risk (3% vs. 2.8%, P = 1.00). CNS relapse cumulative incidence in very elderly treatment‐naive patients is 1.8% at 2 years and is associated with poor survival. This population had a long median time to CNS relapse. Absence of prophylaxis did not strongly impact CNS relapse incidence. Abstract : Cumulative incidence of CNS relapse at 2 years in patients with diffuse large B‐cell lymphoma aged over than 80 is 1.8% and is associated with a very poor survival. The absence of prophylaxis did not appear to have a strong impact on CNS relapse incidence. Consequently CNS prophylaxis can be avoided in this population given the potential for a negative impact of the associated toxicities.